Legal Protection of Trade Secrets over the Potential Disposal of Trade Secrets Under the Re-Engineering Precautions - Faizal Kurniawan; Moch. Marsa Taufiqurrohman; Xavier Nugraha (Jurnal Ilmiah Kebijakan Hukum, 2022)
The Indonesian Trade Secrets Law Number 30/2000 (ITS Law) postulates exemptions for acts that are not considered infringements to protect trade secrets. One of them is the reverse engineering of other people's trade secrets. The problem is that the ITS Law does not limit the extent to which reverse engineering can be justified. The absence of these limitations also allows attempts to disclose trade secrets under the pretext of reverse engineering. This problem ultimately results in the absence of legal certainty for the protection against trade secret disclosure, which is the sole responsibility of the trade secret owner. This article aims to re-analyze the protection provided by the ITS Law and examine the extent to which the limitations on reverse engineering can be justified in the ITS Law. This article used normative juridical research methods combined with statutory, conceptual, and case approaches. It revealed a paradox in the protection of trade secrets against the possibility of trade secret disclosure. This article concluded that changes are necessary to the ITS Law, specifically by adjusting to the basic principles of IPR protection, limiting the extent to which the reverse engineering of other people's trade secrets can be justified, and adding a "Good Faith" clause in performing reverse engineering actions.